2010
DOI: 10.1016/j.exphem.2010.03.002
|View full text |Cite
|
Sign up to set email alerts
|

In vivo generation of β-cell–like cells from CD34+ cells differentiated from human embryonic stem cells

Abstract: Objective-CD34 + cells, present within the bone marrow, have previously been shown to possess pancreatic endocrine potential. Based on this observation, we explored the capacity of CD34 + cells derived in culture from the differentiation of human embryonic stem cells (hESC), for their in-vivo pancreatic endocrine capacity.Methods-Sheep were transplanted with hESC-derived CD34 + cells, as well as non-sorted differentiated cultures. Transplantations were carried out with in-utero intraperitoneal injections prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…One could speculate that CD133/CD34 expression might begin before this point, but evidence supporting this is lacking and needs further investigation. The possibility of restoring lost beta cells by the reprogramming of alpha cells in vivo (Sangan and Tosh 2010;Thorel et al 2010), or by in vitro differentiation form CD34-positive cells derived from human embryonic stem cells (Goodrich et al 2010), is a tantalising thought. CD133/CD34-positive alpha cells may represent a defined source from which insulin-producing cells could be generated, and this is worthy of further study.…”
Section: Discussionmentioning
confidence: 99%
“…One could speculate that CD133/CD34 expression might begin before this point, but evidence supporting this is lacking and needs further investigation. The possibility of restoring lost beta cells by the reprogramming of alpha cells in vivo (Sangan and Tosh 2010;Thorel et al 2010), or by in vitro differentiation form CD34-positive cells derived from human embryonic stem cells (Goodrich et al 2010), is a tantalising thought. CD133/CD34-positive alpha cells may represent a defined source from which insulin-producing cells could be generated, and this is worthy of further study.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue sections were mounted and baked onto slides. Target retrieval using citrate buffer was done as described previously (31). Immunohistochemistry (IHC) was carried out using rabbit anti-SDF1 antibody (clone RB32982) which reacted with both human and sheep tissue sections (Abgent, San Diego, CA), and/or mouse anti-human nuclei antibody (clone 235-1) (PhosphoSolutions, Aurora, CO) which only reacted with human cells.…”
Section: Methodsmentioning
confidence: 99%
“…The present study demonstrated that CD34-and/or CD133-reactive cells contribute to the pancreatic alpha cell population during early fetal development in cattle. It has been previously shown that loss of beta cells can be replaced by alpha cells in vivo (Sangan and Tosh 2010;Thorel et al 2010), or by in vitro differentiation form CD34-positive cells derived from human embryonic stem cells (Goodrich et al 2010). Thus CD133/CD34-positive alpha cells may represent a defined source for insulinproducing cells.…”
Section: Pancreasmentioning
confidence: 96%